Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Community Needs Assessment of Health and Social Services in Notre-Dame-de-Grâce - Holtom, Alexandra (NDG Community Council (NDGCC), 2020)
This community needs assessment is intended to evaluate the assets, weaknesses, gaps, and needs in the NDG community in regards to health and social services. This report describes needs that should be addressed in order to improve the health and well-being of individuals and families living in the NDG community. This community needs assessment provides the NDG Community Council, its stakeholders, and residents with a clearer understanding of health and social service needs in the community. It highlights what local residents, outreach workers, and service providers perceive to be the most pressing needs in the NDG community. This assessment also serves to identify barriers and difficulties when accessing health and social services, particularly those experienced by underserved populations such as youth, seniors, people living with disabilities, visible and racialized minorities, and newcomers, refugees, and asylum seekers living in the NDG community.

Évaluation des besoins de la communauté en matière de santé et des services sociaux à Notre-Dame-de-Grâce - Holtom, Alexandra (NDG Community Council (NDGCC), 2020)
Cette évaluation des besoins de la communauté a été réalisée pour évaluer les atouts, les faiblesses, les lacunes et les besoins de la communauté de NDG en matière de santé et de services sociaux. Ce rapport décrit les besoins qui devraient être adressés afin d'améliorer la santé et le bien-être des individus et des familles vivant dans la communauté de NDG. Cette évaluation des besoins de la communauté permet au Conseil Communautaire de NDG, à ses partenaires, et aux résidents de mieux comprendre les besoins en matière de santé et de services sociaux de la communauté. Elle souligne ce que les résidents locaux, les travailleurs de proximité, et les fournisseurs de services perçoivent comme les besoins les plus urgents de la communauté de NDG. Cette évaluation permet également d'identifier les barrières et les difficultés d'accès aux services sociaux et de santé, en particulier celles rencontrées par les populations sous servies et défavorisées telles que les jeunes, les personnes âgées, les personnes vivant avec un handicap, les minorités visibles et racisées, les nouveaux arrivants, les réfugiés et les demandeurs d'asile vivant dans la communauté de NDG.

Lower North Shore Housing Needs Assessment - Kippen, Kayla (2019)
Communities in rural remote regions often struggle with access to services across the province and other parts of Canada. These access issues are often worsened during times of crisis. A significant problem facing rural communities is the current housing structure for vulnerable people. For example, those requiring palliative care services, or facing mental health and dependency issues, are particularly confronted with issues when trying to secure or obtain stable housing, or access to supportive housing programs and services. In 2017, the federal government announced its first ever National Housing Strategy for Canadians, with a goal of making sure Canadians across the country can access housing that meets their needs and that they can afford. With the witnessed economic downturns, poverty and unemployment rates of the region, it was necessary to investigate whether the Lower North Shore was also providing access to housing that meets the needs of all citizens.

Needs Assessment Report: Providing Resources, Networks, and Representation for English-speaking Youth in Quebec - Youth for Youth Québec (Y4Y Québec) (2019)
Keywords: Official Language Minority Community (OLMC)

Rapport annuel : 2017-2018 - NDG Community Council (NDGCC) (2018)

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
Cette évaluation des besoins a été menée dans le cadre d’un processus de développement communautaire dans la communauté anglophone de Grosse-Île, aux Îles-de-la-Madeleine, Québec. Elle fait partie du suivi d’un portrait communautaire qui a été élaboré par le biais d’un processus participatif au début de 2015. Le processus a impliqué la mobilisation et l’engagement de plusieurs intervenants locaux ainsi que de résidents de la communauté qui ont exprimé leurs opinions sur un bon nombre de thèmes. L’un des enjeux qui a été souligné par les membres de la communauté comme une préoccupation, voire une priorité, était celui du vieillissement de la population au sein de la CAI, ayant peu de services et un soutien limité aux proches aidants.
Keywords: Official Language Minority Community (OLMC)

Women in the STEM Sector - Jedwab, Jack (2016)
Gender-based analysis (hereafter GBA) is defined by Status of Women Canada “a method for examining how an issue is affected by sex, gender, and other intersecting identity factors. It involves examining disaggregated data, as well as social, economic, and cultural conditions and norms.” (GBA: Gender-Based Analysis Plus, SWC 2015). The goal of this project is to conduct a gender-based analysis of the barriers and opportunities faced by women in the Science, Technology, Engineering and Math sector (hereafter STEM), notably when it comes to advancement in their careers. GBA uses sex and gender as entry points to examining an issue, while situating these factors across various identities and experiences. In this report, we focus on the STEM sector, a highly educated group of women from diverse backgrounds, in the Montreal area. We examine this group in relationship to the broader community, as well as focusing on differences across this group, namely in terms of experience within the field.

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

A Needs Assessment : Better Understanding Substance Use Among Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
This needs assessment was requested by the Council for Anglophone Magdalen Islanders (CAMI) in preparation for the development of a strategy to address substance use among young people in Gross-ile, a concern identified by community members.
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : Pour mieux comprendre la toxicomanie chez les jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
Le Council for Anglophone Magdalen Islanders - CAMI (conseil des anglophones des Îles-de-la-Madeleine) a demandé que soit effectuée la présente évaluation des besoins en prévision de l'élaboration d'une stratégie visant à contrer la toxicomanie chez les jeunes, une préoccupation soulevée par des membres de la collectivité.
Keywords: Official Language Minority Community (OLMC)

Westhaven Sector NDG Montreal - NDG Community Council (NDGCC) (2014)
The Westhaven sector is one of the four identified vulnerable sectors in Notre-Dame de Grace. Saint- Jacques and Sherbrooke Street on the East and West and West Broadway and Connaught on the North and South side bind this neighbourhood. The NDG Community Council approached various stakeholders and key actors within the community including residents, volunteers, employees and private storeowners in order to voice their concerns and visions for Westhaven.

The Literacy and Essential Skills Needs of Quebec's Anglophone Adults - Centre for Literacy (CFL) (2012)
Understanding the Literacy and Essential Skills Needs of Quebec’s Anglophone Adults,1 Phase 1, was a project designed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve Englishspeaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities (discussed in detail in Sections Three and Four) which showed large disparities in literacy performance among Quebec Anglophones (Corbeil 2006: 20). The findings suggested differences in needs from one community to another that may require targeted services.

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.

A Needs Assessment on the Issue of Hiring and Retaining English Professionals on the Lower North Shore - Coasters Association (2006)
The Coasters Association, in partnership with the Centre de Santé et de Services Sociaux de la Basse- Côte-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University for seven (7) weeks from February 13 to March 31, 2006, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining Professionals, not only English-speaking - but Bilingual Professionals as well, on the Lower North Shore of Quebec. The objective of this needs assessment was to develop Phase II which is a two year proposal that would lead to the improvement of hiring and retaining professionals on the territory. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the Lower North Shore. Another objective of this needs assessment is to make contact with institutional and community based organizations (ie: Education and H.&S.S.), it is hoped that these contacts will lead to long term partnerships and commitment to addressing the hiring and retention of English and/or Bilingual Professionals on the Lower North Shore.

Needs Assessment & Identification of Opportunities : Fishery Assistance Report - Anderson, Annie-May (Coasters Association, 2004)
Funds were received from the Department of Fisheries and Oceans to assess the needs and identify the opportunities of the fishers and plant workers affected by the closure of the crab in Zone 13, and the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon. With the moratorium imposed on the cod and the closure of the snow crab fishery, the fishers and plant workers were consulted to obtain their views, which will provide a working tool for long term planning for the Coasters Association, Fishermen’s Committees, Municipalities, and Government officials. The first phase of the fishery project began on January 12th, 2004, and finished on May 29th, 2004. The second phase began on May 31st, 2004, and finished on October 1st, 2004. The objective of the project was to identify the issues, opportunities, and the individual needs ofthe fishers and plant workers affected by the closure of the crab in Zone 13, and inshore fishers affected by the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon.

A Needs Assessment Report to Build & Strengthen the Volunteer Base of the Lower North Shore of Quebec - Buckle, Heidi (Coasters Association, 2004)
In the 21st century volunteers are asked to take on roles that hold significant importance. Volunteering is the most fundamental act of citizenship in our society. It is offering time, energy and skills of one’s own free will. By caring and contributing, volunteers decrease disparity, while they can gain skill(s), self-esteem, and can change their lives. People work to improve the lives of their neighbors and, in return, enhance their own. The project’s goal was to identify the needs of the twenty-one (21) regional and one hundred and thirteen (113) community organizations on the coast. The results of the study have provided the population with resourceful information, such as: the mandates, services, and orientation priorities of the regional organizations, the needs of the regional and community groups, and the potential development of new groups/organizations on the Lower North Shore. This was accomplished through a questionnaire (see annex 5) with a 100% success rate of the regional organizations, and a 92% achievement rate for the community organizations. With the development of a survey (see annex 6) and support of the survey participants (see annex 7); a remarkable 100% success rate was established for the potential development of new groups/organizations on the coast. However, it must be said that this information was gathered at the beginning of the project (August-September, 2003) and some of the orientation priorities of the regional organizations maybe completed and/or have changed since then.

Remote Site Information Technology Assessment for the Municipality of Bonne-Esperance Lower North Shore, Quebec - Coasters Association (2004)
Information technologies (computers, Internet, etc.) are an essential component of modern economic development strategies. The Lower North Shore has lagged behind other areas in terms of equipment, infrastructure and human resource capacity for using information technologies as an integral part of their community development efforts (i.e. no hi-speed access.) Recent innovations in this area allow for the reception of hi-speed (broadband) Internet reception via satellite; with establishment of local area networks (LANs) connected to each satellite point-of-delivery, the prospect exists for significant improvements to the information technology capacity of remote locations such as MBE, as well as local revenue generation from service provision once the LAN is established.

Alliance Quebec : A Needs Assessment Study - Alliance Quebec (AQ) (1999)
The pressures of resources - both human and financial – impose limits on studies of this scope that are unavoidable. Furthermore needs are very subjective in nature and may depend upon who identifies them, who evaluates them and where they are placed among other so-called needs. To assess the needs of any particular group as diverse as the community which Alliance Quebec serves is a daunting task. Alliance Quebec's unique provincial perspective clearly underscores that challenge facing all our communities, urban and rural, large and small, unilingual and multi-lingual. English-speaking Quebecers are increasingly ethnically diverse, ageing and in fear of the loss of our young to other parts of the country and the world. Obviously, given these circumstances, differences will surface as to what is a need and as to how the needs are to be determined. Even though we face common issues, there is nothing common about the way our communities face those issues.

English-speaking Communities of Quebec : Needs Identification Document - Alliance Quebec (AQ) (1981)
"If Quebec's Anglophone - or better, non-Francophones - feel isolated and insecure, it is precisely because they are not the monolithic and plutocratic leviathan of popular culture. And if they do not avail themselves much of the Official Languages Act, it is not because the federal performance in Quebec is impeccable, but becuase the relevance of the law to their situation has been very slow to get through." (1979 Annual Report of the Federal Commissioner of Official Languages, page 24).